High-Shear Stress Sensitizes Platelets to Subsequent Low-Shear Conditions - Sheriff, Jawaad (2010)
Individuals with mechanical heart valve implants are plagued by flow-induced thromboembolic complications, which are undoubtedly caused by platelet activation. Flow fields in or around the affected regions involve brief exposure to pathologically high-shear stresses on the order of 100 to 1000 dyne/cm(2). Although high shear is known to activate platelets directly, their subsequent behavior is not known. We hypothesize that the post-high-shear activation behavior of platelets is particularly relevant in understanding the increased thrombotic risk associated with blood-recirculating prosthetic cardiovascular devices. Purified platelets were exposed to brief (5–40 s) periods of high-shear stress, and then exposed to longer periods (15–60 min) of low shear. Their activation state was measured using a prothrombinase-based assay. Platelets briefly exposed to an initial high-shear stress (e.g., 60 dyne/cm(2) for 40 s) activate a little, but this study shows that they are now sensitized, and when exposed to subsequent low shear stress, they activate at least 20-fold faster than platelets not initially exposed to high shear. The results show that platelets in vitro exposed beyond a threshold of high-shear stress are primed for subsequent activation under normal cardiovascular circulation conditions, and they do not recover from the initial high-shear insult.